Association of oral manifestations with ulcerative colitis - Elahi, Maryam (Research Institute for Gastroenterology and Liver Diseases, 2012)
AIM: The study aims to document the oral lesions in patients with UC. BACKGROUND: Inflammatory bowel disease (IBD) is comprised of two chronic, tissue-destructive and clinical entities including Crohn's disease (CD) and ulcerative colitis (UC), both of which are immunologically based. PATIENTS AND METHODS: The population of the study includes fifty patients with UC, as the experimental group, and fifty patients without gastrointestinal disease as the control group. All patients had an oral examination and completed the relevant questionnaire. RESULTS: There was a significant statistical relationship among tongue coating (<0.0001), halitosis (<0.0001), and oral ulceration (0.001) in patients suffering from severe UC compared to the control group. Also there was a higher prevalence of oral manifestations in patients with moderate UC compared to that of control group; but taste change (0.001) was the only significant factor. Acidic taste and taste change were among the symptoms more commonly found in patients suffering from pancolitis (40% each). CONCLUSION: The results of the present study show that patients with UC had more oral signs and symptoms than the patients in the normal group. Further researches on oral lesions in UC are also recommended so that these diseases can be better understood.